Development and implementation of a community health literacy hub, ‘Health Kiosk'—A grassroots innovation - Masquillier, Caroline; Van Royen, Kathleen; Van Pelt, Patricia; Onsea, Dorien; Bastiaens, Hilde (Frontiers in Public Health, 2023)
Being health literate is important to get sufficient health information, to navigate the health system, to access appropriate care and to be able to self-manage health. As such it is a key determinant of health. There is a need for innovative measures to improve health literacy among people living in socioeconomically vulnerable circumstances. Literature shows that this innovation needs to: have “low-threshold access” to health resources in a community-based, outreaching way; be adapted to the needs of the target group; provide reliable and understandable health information adapted to the target population, and support people in developing confidence to act on that knowledge. In response to this need, this article describes—guided by the principles underpinning the Integrated Community Care (ICC) framework—the development and implementation process of a grassroots innovation, namely “Health Kiosk” in a socioeconomically vulnerable area in the northern part of a Belgian city. To be able to focus on the core activity of the Health Kiosk—i.e., stimulating healthy living and health literacy—community building and considering the spatial environment of the neighbourhood formed a fundamental basis. Several core ingredients of the Health Kiosk are important to stimulate health literacy among socioeconomically vulnerable groups, namely: (1) working in a community-based, outreaching way; (2) providing accessible health information and support to act on that knowledge; and (3) working in a flexible and independent way to adapt to local needs. As such, the Health Kiosk forms a community health literacy hub with low-threshold access for people living in socioeconomically vulnerable circumstances.